IMPOSSIBLE OBJECTS! SPACE-TIME EXPERIENCE OF ARCHITECTURAL HERITAGE - Joaquim Santos (European Scientific Journal, ESJ, 2015)
Rose Seidler House is a particularly impressive house that is witness to the strength of the Modern Movement world wide. The neoplastic reference is obvious and it is a personal construction of the whole architectural space. From the environment the house stands on the articulation of the inner-outer spaces and we may easily realise that we are inside an impressive architectural masterpiece. Yet, the place where Rose Seidler lived surrounded by the upper most comfortable environment found its new destiny, a museum. Thus, like other architectural masterpieces, its perfection made the place impossible to live in. The touristic attraction now dictates the destiny of the house. And writing about it from a personal point of view may mean that we may treat architecture in general as tourists looking for pure architectural experience. Thus, tourism does not only frame important issues such as new uses from old buildings and cultural heritage perspectives, but it can also give us a particular view of everything and anything. Thus, we may tend to operate within a world made up of partial limited views that, nonetheless, we read as universal.